2020
DOI: 10.1038/s41598-020-61716-6
|View full text |Cite
|
Sign up to set email alerts
|

Landscape factors influencing honey bee colony behavior in Southern California commercial apiaries

Abstract: Colony brood levels, frames of bees (adult bee mass) and internal hive temperature were monitored for 60 colonies for each of two years as they were moved from agricultural, tree crop and mountain landscapes in southern California to blueberry and almond pollination sites. Hive weight was also continuously monitored for 20 of those hives for 6 weeks for both years, during commercial pollination. Pesticide residues in wax, honey and beebread samples were analyzed by composite apiary samples. While colonies in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Environmental variability among experiments may have made effects due to pesticide exposure harder to detect. Results from MS 2018 were consistent with studies conducted in the southern half of the U.S. that have shown higher growth rates, better thermoregulation and lower pathogen loads for bee colonies kept in landscapes with some agriculture compared to those kept in other landscapes (urban, peri-urban, or completely unmanaged, depending on the study) 53 55 . The amount of agriculture within a 1.8 km radius of the Mississippi site was not high, but the density and diversity of honey bee forage was clearly higher than in southern Arizona.…”
Section: Discussionsupporting
confidence: 83%
“…Environmental variability among experiments may have made effects due to pesticide exposure harder to detect. Results from MS 2018 were consistent with studies conducted in the southern half of the U.S. that have shown higher growth rates, better thermoregulation and lower pathogen loads for bee colonies kept in landscapes with some agriculture compared to those kept in other landscapes (urban, peri-urban, or completely unmanaged, depending on the study) 53 55 . The amount of agriculture within a 1.8 km radius of the Mississippi site was not high, but the density and diversity of honey bee forage was clearly higher than in southern Arizona.…”
Section: Discussionsupporting
confidence: 83%
“…Different landscape factors and pesticide exposure can influence colony thermoregulation. , In this study, we found that differences in hive temperature data corresponded to feed manipulations in a commercial beekeeping operation. This finding highlights the potential of sensor data to inform future studies and management practices related to supplemental feeding, especially in large-scale beekeeping operations.…”
Section: Discussionmentioning
confidence: 67%
“…Two of these experiments were located in Sydney, Australia, and received an experimental treatment (pesticide or control, food stores removal or control) to reproduce environmental stress, while in the third experiment hives were located in California, USA and not subject to any treatments but were dispatched in different crops and were managed independently by a beekeeper 19 .…”
Section: Sitesmentioning
confidence: 99%